The role of radiology in diagnosing synchronous subglottic and mediastinal haemangioma: a rare clinical entity - Yasar, Yunus; Betul Demircan Coskun; Bag, Ozlem (Journal of the Pakistan Medical Association, 2025)
Subglottic haemangioma is a rare and life-threatening condition in infancy. A four-month-old girl presented with cough and wheezing with a history of three prior hospitalisations for bronchiolitis and inspiratory stridor. An upper airway endoscopy and imaging, including ultrasonography, CT scan, and MRI, revealed synchronous subglottis and mediastinal haemangioma. She responded to oral Propranolol treatment with complete resolution within six months of initiating therapy. Subglottic haemangiomas should be considered in infants with recurrent airway symptoms and obstruction. Keywords: Subglottic haemangioma, Airway obstruction, Infant, Computed tomography, Magnetic resonance.